Better by bus? Insights into public transport travel behaviour during Storm Doris in Reading, UK. (23rd November 2017) - Budnitz, Hannah; Chapman, Lee; Tranos, Emmanouil
Abstract : This case study uses datasets from Reading Buses' electronic ticketing system to gain insights into the reactions of public transport passengers to the disruption to bus and rail services in Reading, UK during Storm Doris on 23 February 2017. The analysis generally supports previous research findings that there are fewer public transport trips in adverse weather conditions. However, an increase in bus trips on services parallel to the more severely disrupted train services suggests that some travellers respond flexibly by using the bus as an alternative, more resilient mode. Abstract : High winds during winter storms like the one that hit the UK on 23 February 2017 are a major risk to transport infrastructure, particularly rail. Passengers' journeys can be severely disrupted, but data from Reading Buses provide further evidence that discretionary public transport trips may be cancelled, whilst commuters respond more flexibly, for example by changing the timing of their journeys. The data also suggest that rail passengers switch to buses as an alternative, more resilient mode in severe weather.